1999
DOI: 10.1076/noph.21.4.233.3892
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-ophthalmological presentation of pneumosinus dilatans

Abstract: Pneumosinus dilatans (PSD) is a rare disease characterized by an abnormal expansion of an air-filled paranasal sinus. Because of the pressure effect on the adjacent structures, PSD may present with several neurological signs, the ocular ones being the most common. In the present study, we describe a case of frontal PSD with diplopia, proptosis, ophthalmoplegia, and compressive optic neuropathy. Imaging showed a large amount of air in the right orbit continuous with the ipsilateral frontal sinus. Endoscopic sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…Candan et al demonstrated an increase in intrasinus pressure caused by a non-return valve mechanism [19]. Carta et al reported a case of PD with diplopia, proptosis, ophthalmoplegia, and compressive optic neuropathy [20]. The authors attributed amaurosis to changes in atmospheric pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Candan et al demonstrated an increase in intrasinus pressure caused by a non-return valve mechanism [19]. Carta et al reported a case of PD with diplopia, proptosis, ophthalmoplegia, and compressive optic neuropathy [20]. The authors attributed amaurosis to changes in atmospheric pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Várias complicações neurooftalmológicas tem sido descritas no PSD, como neuropatia óptica compressiva, proptose, diplopia, dor periocular e oftalmoplegia. Carta et al (13) publicaram um caso de um paciente de 72 anos de idade que apresentou perda de visão progressiva, proptose e diplopia. A TC demonstrou grande quantidade de ar na órbita direita em continuidade com o seio frontal ipsilateral.…”
Section: Neuropatia óPtica Compressivaunclassified